Entrepreneurship Education and Entrepreneurial Intentions of College Students: The Mediating Role of Entrepreneurial Self-Efficacy and the Moderating Role of Entrepreneurial Competition Experience - Wu, Lihao; Jiang, Suo; Wang, Xiaomin; Yu, Linwei; Wang, Yansu; Pan, Hui (Frontiers in Psychology, 2022)
This study aims to promote college students to actively participate in entrepreneurship competitions and social practice, cultivate their entrepreneurial skills and practical ability, and explore effective ways to improve college students’ entrepreneurial self-efficacy and intentions through entrepreneurship education. The survey used a random sample of 804 college students in Zhejiang Province, China. The results show that: (1) from the characteristics of entrepreneurial intention, there are significant differences in gender, entrepreneurial experience, entrepreneurial competition experience and family background of self-employment. (2) There are significant differences in the characteristics of entrepreneurship education in gender, entrepreneurial competition experience, and the family background of self-employment. (3) In the relationship among entrepreneurship education, entrepreneurship self-efficacy and entrepreneurship intention, entrepreneurship education is significantly and positively related to entrepreneurship self-efficacy and entrepreneurship intention. Entrepreneurial self-efficacy is significantly and positively associated with entrepreneurial intention. Entrepreneurial self-efficacy plays a complete mediating role between entrepreneurship education and entrepreneurial intention. Entrepreneurial self-efficacy also has a suppressing effect on the relationship between the two. (4) Entrepreneurial competition experience moderates the second half of the mediating effect of entrepreneurial self-efficacy. Finally, the study offers several proposals for the teaching practice of entrepreneurship education.